Bearing Repair and Monitoring for Poyanghu Cable-Stayed Bridge - X. X. Cheng; F. B. Ma; J. Q. Chen; B. Dong; G. Wu (Advances in Civil Engineering)
Currently, the bearings of Poyanghu Bridge, a 636-meter long cable-stayed bridge, have been damaged. According to numerical analyses, the mechanical state of the damaged bridge unfavorably deviates from the ideal design state, and the bridge should be repaired in time to restore its safety and serviceability. However, compared with the bearing repair of beam bridges, much less scientific and engineering endeavors have been made in the history to direct the bearing repair of cable-stayed bridges. This article proposes two innovative bearing repair schemes for cable-stayed bridges and reports the numerical validations, the on-location applications, and the monitoring of the proposed repair schemes under the engineering backgxround of Poyanghu Bridge. Through these works, it is found that the proposed repair schemes are effective in practical use.